Graph theory approach to prices transmission in the network of commonly used liquid fuels - Karel Janda; Barbora Schererova; Jan Sila; David Zilberman (Charles University in Prague, Institute of Economic Studies (IES), 2023)
We analyze the relationships within the liquid fuels system and its associated supply chain using innovative network filtering methods, namely the Minimum Spanning Tree and Triangulated Maximally Filtered Graph. Our findings reveal that biofuels form robust connections with their feedstocks that intensify during periods of economic or legislative uncertainty. Conversely, fossil fuels form detached clusters primarily influenced by global economic conditions. These insights significantly enhance our understanding of the liquid fuels market dynamics and suggest potential avenues for integrating additional liquid fuels into the supply chain network.
Keywords: C38; Q41; Q55; 330; fossil fuels; biofuels; crude oil; complex network analysis; community detection; triangulated maximally filtered graph; minimum spanning tree; relationship analysis